LITERATURE REVIEW: KAJIAN EFEKTIVITAS PERKEMBANGAN VAKSIN VIRUS DENGUE MASA KINI - Aulia, Tisa (UNIVERSITAS BENGKULU, 2024)
Dengue fever is a disease caused by the dengue virus (DENV) which often becomes a problem for public health in the world with approximately 390 million cases of infection. The lack of specific antiviral therapy for DENV is a driving force for the development of a dengue vaccine as a strategy to fight the DENV virus. This review discusses the development of dengue vaccines and makes effectivity comparisons with dengue vaccines that have been developed such as Dengvaxia, TV003/TV005, and DENVax to know the current status of the development of these vaccines. Keywords : Dengue fever, Dengue Virus, vaccines, development, effectivity